PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT DISTRIVERSA BUANAMAS CABANG MAMPANG - Izatil Isma, Zahra; Purnama, Aan (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence of work discipline and work environment on employee performance at PT Distriversa Buanamas Mampang Branch. The method used was a quantitative approach and using the Slovin formula, a sample of 52 respondents was obtained. The analysis method uses Validity Test, Reliability Test, Classical Assumption Test, Regression Analysis, Correlation Coefficient Test, Determination Coefficient Test and Hypothesis Test. The data analysis of this study uses the SPSS version 26 program. Work discipline (X1) has a positive effect on Performance (Y) obtained the result of the regression equation value Y = 12.198 + 0.699 XI, the correlation coefficient is 0.790 meaning that the two variables have a strong relationship level. The value of determination or contribution is 62.4% while the remaining 37.6% is influenced by other factors. The hypothesis test obtained a t-value calculated > t table or (9.113 > 0.273) strengthened by a ρ value < Sig.0.05 or (0.000 < 0.05), thus Ho1 was rejected and Ha1 was accepted. Work Environment (X2) has a positive effect on Performance (Y) obtained the result of the equation value Y = 16.197 + 0.611 X2, the correlation coefficient is 0.740 meaning that the two variables have a strong relationship level. The value of determination or contribution is 54.8% while the remaining 45.2% is influenced by other factors. The hypothesis test was obtained with a calculated t-value > t table or (7.785 > 0.273) strengthened by a ρ value < Sig.0.05 or (0.000 < 0.05), thus Ho2 was rejected and Ha2 was accepted. Work Discipline (X1) and Work Environment (X2) have a positive effect on Performance (Y) obtained the result of the equation value Y = 12.231 + 0.632 X1 + 0.068 X2 and the correlation coefficient value of 0.791 means that the two variables have a strong relationship level. The determination value was 62.5% while the remaining 37.5% was influenced by other factors. The hypothesis test was obtained with a value of f calculated > f table or (40.871 > 3.19) strengthened by a ρ value < Sig.0.05 or (0.000 < 0.05), thus Ho3 was rejected and Ha3 was accepted.